Cord Blood Banking: Antenatal Care Provider's Roles and Responsibilities - Vishal Gupta; Lipisha Agarwal; Priya Ballal; Deeksha Pandey (Hindawi Limited, 2019)
Background. Umbilical Cord Blood (UCB) banking done either for private storage or for donation to public cord blood banks involves active participation of obstetricians. Counseling the expectant parents, providing them with unbiased and balanced information, and collecting the UCB with diligence confer a lot of social as well as moral responsibility upon obstetricians. This makes it even more important that the obstetricians in current practice stay well-informed and updated with UCB collection and its storage guidelines. The present study was conducted to assess the current status of obstetricians about UCB banking in terms of their awareness, attitude, and expectations from it. Materials and Methods. A cross-sectional study was conducted across three hospitals. A self-administered 22-item questionnaire was given to obstetricians to assess their awareness, attitude, and expectations about UCB banking. Finally, 154 completed questionnaires were analyzed using SPSS software (version 15.0). The awareness, attitude, and expectations were assessed and reported as primary endpoints and the self-rated knowledge levels, and sources of information were reported as secondary endpoints. Results. Overall, the awareness was poor, but the attitude was favorable for UCB banking amongst obstetricians. Around 74% felt that obstetricians must be well-informed about UCB banking-related counseling and collection protocols. However, 55% felt it to be an additional burden for the obstetrician, and 57% believed that financial compensation must be given to obstetricians involved with cord blood collection procedures. The majority remained unclear about their expectations from UCB banking. The self-rated knowledge was poor and very poor for 75% obstetricians. 89.6% derived their information from representatives of private cord blood companies. Conclusion. Although poor in awareness levels, obstetricians possessed a favorable attitude towards UCB banking. Continuing medical education needs to focus more on such current issues of public importance to keep professionals updated. This is one way to minimise percolation of wrong facts and figures by the industries with conflicting interest to the healthcare providers.